THE EFFECT OF QUALITY OF SERVICE, IMAGE, AND BUSINESS ETHICS ON SATISFACTION AND LOYALITY OF PATIENTS IN HOSPITALS IN MAKASSAR CITY - Azhari, Aslan; Modding, Basri; Labbase, Ilham; Plyriadi, Annas (Institute for Research and Community Service, 2020)
Research related to the Effect of Service Quality, Image, and Business Ethics on Patient Satisfaction and Loyalty at Hospitals in Makassar City. This research was conducted which aims to: (1) test and analyze the effect of service quality, image, business ethics on patient satisfaction, (2) test and analyze the effect of service quality, image, business ethics on patient loyalty, (3) test and analyze the effect satisfaction with patient loyalty, (4) test and analyze the indirect effect of service quality, image, and business ethics on patient loyalty through mediating patient satisfaction. This study uses primary data through distributing questionnaires to a total of 203 inpatients as samples from the total number of patients in 2018 totaling 69.337, data collection was carried out from December 2019 to January 2020. Data were analyzed using Structural Equation Modeling (SEM) analysis with program assistance AMOS and SPSS. The results showed that (1) service quality, image, and business ethics had a positive and significant direct effect on patient satisfaction, (2) service quality, image, and business ethics had a positive and significant direct effect on patient loyalty, (3) satisfaction has a positive and not significant direct effect on patient loyalty, (4) an indirect relationship of service quality, image, and business ethics, through mediation satisfaction has a positive and not significant effect on patient loyalty. This means that the provision of good quality services, the application of the hospital's image, and the application of ethical behavior will have a direct role in patient satisfaction and loyalty. Patient satisfaction does not significantly affect patient loyalty due to the existence of a system of tiered referral system which makes it impossible for patients to directly choose the hospital, except in an emergency. Quality of service, image, and business ethics through satisfaction has a positive and not significant effect on patient loyalty. This shows that patient satisfaction is not able to mediate to have a significant influence on patient loyalty.